AATF: A new actor in the complex world of mTOR - Fanciulli, Maurizio (Mol Cell Oncol, 2015)
Reflecting the pivotal role of mammalian target of rapamycin (mTOR) in the cell, a number of pathways, several of which exhibit changes in expression or activity in different cancers, tightly control its activation. We have recently demonstrated that antiapoptotic transcription factor (AATF) regulates mTOR in response to several kinds of stress.